Structural health monitoring on medium rise reinforced concrete building using ambient vibration method - Kamarudin, A. F.; Mokhatar, S. N.; Zainal Abidin, M. H.; Daud, M. E.; Rosli, M. S.; Ibrahim, A.; Ibrahim, Z.; Md Noh, M. S. (2018)
Monitoring of structural health from initial stage of building construction to its serviceability is an ideal practise to assess for any structural defects or damages. Structural integrity could be intruded by natural destruction or structural deterioration, and worse if without remedy action on monitoring, building re-assessment or maintenance is taken. In this study the application of ambient vibration (AV) testing is utilized to evaluate the health of eighth stories medium rise reinforced concrete building in Universiti Tun Hussein Onn Malaysia (UTHM), based comparison made between the predominant frequency, fo, determined in year 2012 and 2017. For determination of fo, popular method of Fourier Amplitude Spectra (FAS) was used to transform the ambient vibration time series by using 1 Hz tri-axial seismometer sensors and CitySharkII data recorder. From the results, it shows the first mode frequencies from FAS curves indicate at 2.04 Hz in 2012 and 1.97 Hz in 2017 with only 3.14% of frequency reduction. However, steady state frequencies shown at the second and third modes frequencies of 2.42 Hz and 3.31 Hz by both years. Two translation mode shapes were found at the first and second mode frequencies in the North-South (NS-parallel to building transverse axis) and East-West (EsW-parallel to building longitudinal axis) components, and the torsional mode shape shows as the third mode frequency in both years. No excessive deformation amplitude was found at any selective floors based on comparison made between three mode shapes produced, that could bring to potential feature of structural deterioration. Low percentages of natural frequency disparity within five years of duration interval shown by the first mode frequencies under ambient vibration technique was considered in good health state, according to previous researchers recommendation at acceptable percentages below 5 to 10% over the years.